2020
DOI: 10.5194/gmd-2020-65
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CoupModel (v6.0): an ecosystem model for coupled phosphorus, nitrogen and carbon dynamics – evaluated against empirical data from a climatic and fertility gradient in Sweden

Abstract: Abstract. This study presents the integration of the phosphorus (P) cycle into CoupModel (Coup-CNP). The extended Coup-CNP enables simulations of coupled carbon (C), nitrogen (N) and P dynamics for terrestrial ecosystems which explicitly consider mycorrhizal interactions. The model was evaluated against observed forest growth and measured leaf C/P, C/N and N/P ratios in four managed forest regions in Sweden. The four regions form a climatic and fertility gradient from 64° N in the North to 56° N in South Swede… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…The main structure is a one-dimensional, vertical model, with one or two layers of vegetation (e.g., a shrub and moss layer as in this application) on a multi-layered soil profile. In this application, we used the most recent model version (v.6) from He et al (2021), but without nitrogen and phosphorus cycles. The model is driven by measured climatic data -precipitation, air temperature, relative humidity, wind speed, and global radiation.…”
Section: Brief Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main structure is a one-dimensional, vertical model, with one or two layers of vegetation (e.g., a shrub and moss layer as in this application) on a multi-layered soil profile. In this application, we used the most recent model version (v.6) from He et al (2021), but without nitrogen and phosphorus cycles. The model is driven by measured climatic data -precipitation, air temperature, relative humidity, wind speed, and global radiation.…”
Section: Brief Model Descriptionmentioning
confidence: 99%
“…To link the varying boundary conditions and the associated CO 2 dynamics, the processbased CoupModel was used. We chose CoupModel (Jansson, 2012;He et al, 2021) because it includes detailed soil physics, hydrology, photosynthesis, and ecosystem respiration (ER) that can simulate the association of the peatland C dynamics with vertical and lateral hydrology flow (He et al, 2016). Furthermore, past studies have shown that the model can successfully simulate the C dynamics, the energy and water balance of managed European treeless peatlands (Metzger et al, 2015), but as yet it has not been applied to continental bogs.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are emerging approaches to representing mycorrhizal P i uptake explicitly. For instance, in the Coup-CNP model, plants allocate C to fungi as long as the P i return is advantageous (He et al, 2021). The fungi can explore both the available P i pool and P o pool, but ultimately P i uptake is limited by the fungal biomass (He et al, 2021).…”
Section: Plant P-use and -Acquisition Strategiesmentioning
confidence: 99%
“…For instance, in the Coup-CNP model, plants allocate C to fungi as long as the P i return is advantageous (He et al, 2021). The fungi can explore both the available P i pool and P o pool, but ultimately P i uptake is limited by the fungal biomass (He et al, 2021). Moreover, vegetation models are designed for modeling large-scale vegetation dynamics; consequently, the challenge lies in finding generalities of microscale dynamics occurring at the root surface that allow upscaling along resource gradients and projecting impacts of global change at the ecosystem scale.…”
Section: Plant P-use and -Acquisition Strategiesmentioning
confidence: 99%
“…5). Therefore, we think that our straightforward approach to estimate water management strategy ef-fectivity forms an alternative approach of intermediate complexity compared to either groundwater-table-CO 2 emission relationships (Couwenberg et al, 2011;Fritz et al, 2017;Tiemeyer et al, 2020;Arets et al, 2020;Evans et al, 2021) or models that resolve the entire carbon cycle (van Huissteden et al, 2006;He et al, 2021). The additional complexity of unsaturated zone modelling of water flow and introducing soil temperature and WFPS-activity curves requires a considerably higher modelling effort compared to approaches that rely on relationships between yearly average groundwater table and CO 2 emissions, but it allows us to investigate the effect differences between groundwater levels raised by ditchwater level manipulations or by applying SSI.…”
Section: Simulated Versus Observed Dynamics and Ssi Effectsmentioning
confidence: 99%